DESAIN KEMASAN PRODUK DENGAN CANVA: PELATIHAN UNTUK KELOMPOK TANI PUTRA FARM COMPANY DI DESA TAMBUN RAYA - Din Permadi, Pradana; Setiawati, Nani; Thomas, Orbit; Yedithia, Fenroy; Novan, Christian; Agustina, Lisa; Putri Pitaloka, Whilis; Toendan, Krisnayadi; Efriani, Efriani; Utami, Lakamitha; Enjelina , Maria (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Packaging design is a crucial aspect of product development because it plays a significant role in enhancing product appeal and expanding market reach. However, many businesses, particularly micro, small, and medium enterprises (MSMEs), still face limitations in comprehensive packaging design. This community service activity aims to improve the graphic design skills of members of the Putra Farm Company Farmers Group in Tambun Raya Village, Central Kalimantan, through training on the use of the Canva application in creating product packaging designs. The method used was a participatory approach through the stages of problem identification, training material development, training implementation, evaluation, mentoring, and documentation. The training results showed a significant increase in participants' ability to use Canva, with all participants able to produce product packaging designs independently. Improvements were also seen in their understanding of the importance of packaging in marketing and the competitiveness of local products. This activity has had a positive impact on market expansion and increasing the selling value of the farmer group's products. This program demonstrates that utilizing simple and accessible graphic design technology like Canva can be an effective solution to support the economic independence of rural communities.